Temporal Variability in Surface Water pCO2 in Adventfjorden (West Spitsbergen) With Emphasis on Physical and Biogeochemical Drivers. Issue 7 (17th July 2018) - Ericson, Y.; Falck, E.; Chierici, M.; Fransson, A.; Kristiansen, S.; Platt, S. M.; Hermansen, O.; Myhre, C. L.
Abstract: Seasonal and interannual variability in surface water partial pressure of CO2 ( p CO2 ) and air‐sea CO2 fluxes from a West Spitsbergen fjord (IsA Station, Adventfjorden) are presented, and the associated driving forces are evaluated. Marine CO2 system data together with temperature, salinity, and nutrients, were collected at the IsA Station between March 2015 and June 2017. The surface waters were undersaturated in p CO2 with respect to atmospheric p CO2 all year round. The effects of biological activity (primary production/respiration) followed by thermal forcing on p CO2 were the most important drivers on a seasonal scale. The ocean was a sink for atmospheric CO2 with annual air‐sea CO2 fluxes of −36 ± 2 and −31 ± 2 g C·m −2 ·year −1 for 2015–2016 and 2016–2017, respectively, as estimated from the month of April. Waters of an Arctic origin dominated in 2015 and were replaced in 2016 by waters of a transformed Atlantic source. The CO2 uptake rates over the period of Arctic origin waters were significantly higher (2 mmol C·m −2 ·day −1 ) than the rates of the Atlantic origin waters of the following year. Key Points: Large undersaturation of surface water p CO2 with respect to atmospheric p CO2 was observed in an Arctic fjord following two annual cycles Biological activity and temperature are key drivers for the observed monthly variability in surface water p CO2 The uptake of CO2 is enhanced when Arctic origin waters are present in the fjord as compared to Atlantic origin waters